Simulation of Time-Lapse Resistivity Method on Sandbox Model to Determine Fluid Changes and Desaturation - Rizka Rizka; Beta Arroma Piskora; Soni Satiawan; Hendra Saputra (UIR PRESS, 2020)
Time-lapse resistivity method is an implementation of the resistivity method that is executed exactly at the same spot but with various in time. In this study, the technique uses to identify the dynamics of groundwater fluids. The application of the time-lapse resistivity method was carried out by performing a sandbox model simulation that contains layers of rocks with a fault structure. The rock layers consist of tuff, fine sandstone, shale, coarse sandstone, gravel that represents confined and unconfined aquifers. The simulation was achieved by applying the Electrical Resistivity Tomography (ERT) dipole-dipole configuration at the same place, and measurements with 3 different conditions, namely dry, wet conditions filled with 2.5% water and wet conditions filled with 5% water. Data acquisition uses Naniura resistivity meters with a track length of 96 cm. The first measurement results (dry conditions) obtained a range of resistivity values ​​from 3.7 to 168.1 Ω.m, the second measurement (wet conditions filled 2.5% water) obtained the range of resistivity values ​​from 3.3 to 110.8 Ω.m and the third measurement (wet conditions) filled with 5% water the resistivity values ​​range from 1.7 to 91.2 Ω.m. Following the results of time-lapse inversion processing, a larger percentage change in the amount of 5.6% due to water absorption by the surface which then migrates into the inner layer. Whereas the percentage of desaturation ranges is from -3.11 to 0.217 %, refer to Archie’s Law assumes conduction is caused by water content.